Highly improved dielectric behaviour of ferronematic nanocomposite for display application. Issue 5 (9th April 2019) - P. J, Jessy; S., Radha; Patel, Nainesh
ABSTRACT: We report the investigation of influence of nickel zinc ferrite magnetic nanoparticles (NZFO (Ni0.5 Zn0.5 Fe2 O4 )) on phase transition, optical and dielectric properties in a nematic liquid crystal (NLC). The interaction of NZFO nanoparticles with NLC was confirmed by the formation of ferronematic droplets due to the transfer of magnetic orientational effect onto the underlying NLC matrix. The doping results in shift of nematic to isotropic transition to low-temperature region. An enhancement in the value of refractive index is observed in the nematic region after the addition of NZFO nanoparticles. The dielectric constant of NLC was remarkably enhanced by 10 times after doping, which is found to be maximum at 0.1 wt% concentration of NZFO nanoparticles. The decrease in the value of dissipation factor in low-frequency region shows that the magnetic nanoparticles are able to trap ionic impurities effectively. The obtained results suggest that the optimum amount of doping concentration is 0.1 wt% of NZFO nanoparticles in NLC due to high dielectric constant with low dissipation factor and high refractive index with high dispersive power at room temperature. Graphical Abstract: